2019
DOI: 10.1111/mec.15256
|View full text |Cite
|
Sign up to set email alerts
|

The role of recombination on genome‐wide patterns of local ancestry exemplified by supplemented brook charr populations

Abstract: Assessing the immediate and long‐term evolutionary consequences of human‐mediated hybridization is of major concern for conservation biology. Several studies have documented how selection in interaction with recombination modulates introgression at a genome‐wide scale, but few have considered the dynamics of this process within and among chromosomes. Here, we used an exploited freshwater fish, the brook charr (Salvelinus fontinalis), for which decades of stocking practices have resulted in admixture between wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Hybrid genomes exhibit a mosaic of ancestry from their parental populations. A number of recent studies have shown that hybridization interacts with recombination and selection to shape patterns of local ancestry along chromosomes ( Hohenlohe et al., 2012 ; Wang et al., 2016 ; Janzen et al., 2018 ; Schumer et al., 2018 ; Leitwein et al., 2019 ). Non-random distributions of local ancestry in hybrid populations can indicate selection.…”
Section: Methodsmentioning
confidence: 99%
“…Hybrid genomes exhibit a mosaic of ancestry from their parental populations. A number of recent studies have shown that hybridization interacts with recombination and selection to shape patterns of local ancestry along chromosomes ( Hohenlohe et al., 2012 ; Wang et al., 2016 ; Janzen et al., 2018 ; Schumer et al., 2018 ; Leitwein et al., 2019 ). Non-random distributions of local ancestry in hybrid populations can indicate selection.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, mapping genomic data onto a reference genome assembly can identify chromosomal tracts of ancestry. Because these blocks of ancestry break down through recombination following a hybridization event, the distribution of their sizes can be used to infer the history of hybridization and admixture in wildlife species, as well as evidence for selection in admixed genomes (e.g., Leitwein et al, 2018Leitwein et al, , 2019. long-term viability, potential for increases in distribution or population size, and extinction probability.…”
Section: Hybridization and Admixturementioning
confidence: 99%
“…Hybrid genomes exhibit a mosaic of ancestry from their parental populations. A number of recent studies have shown that hybridization interacts with recombination and selection to shape patterns of local ancestry along chromosomes [83][84][85][86][87] . Non-random distributions of local ancestry in hybrid populations can indicate selection.…”
Section: Local Ancestry Inferencementioning
confidence: 99%